A nomenclator of Ficus sect. Americanae (Moraceae). Part II: North and Central America, and the Antilles - Mitidieri-Rivera, Nicole; Damián-Parizaca, Alexander; Gardner, Elliot; Pederneiras, Leandro C. (Phytotaxa, 2026)
Typification underpins the stability of nomenclature, thereby making coherent taxonomic discourse possible. As part of ongoing systematic studies in Ficus sect. Americanae (Moraceae), we present the second installment of a two-part nomenclatural treatment addressing all published names within the section. The first part encompassed species described from South America, while the present contribution focuses on names from North and Central America and the Antilles. Across both treatments, we examined the relevant literature and critically assessed type vouchers for taxa described from the Linnaean era to the present. In this work, we designate 28 lectotypes, two neotypes, and two epitypes. Nomenclatural adjustments include the correction of holotype to lectotype for 24 names (ICN, Art. 9.12) and type to lectotype for four names (ICN, Art. 9.17), with the term type corrected to neotype for F. lentiginosa var. imrayana and F. eximia var. cubensis. We also designate epitypes for F. americana and F. citrifolia. These revisions provide the necessary nomenclatural stability to support the accurate application of names to phylogenetically delimited clades in forthcoming integrative treatments of Ficus sect. Americanae. Together, both indexes constitute an authoritative reference that establishes a framework for taxonomic and systematic stability and accuracy in Ficus, both regionally and globally.